Charity advertising: congruence between political orientation and cause of need. Issue 7 (2nd October 2020) - Lee, Younghwa; Seo, Joon Yong; Yoon, Sukki
Abstract: Philanthropic appeals are more persuasive if messages match the processing styles of potential donors. To help marketers design more congruent charity appeals, the authors conduct two experiments testing a new type of congruence: political orientations that determine donor reactions to charity appeals for alleviating poverty. Korean student samples are used in a 2 (political orientation: conservatives and liberals) X 2 (causes of need: internal/dispositional and external/social) between-subjects design. Findings show that liberal donors respond more favourably to appeals that use external attributions blaming social causes, and conservative donors respond more favourably to appeals that use internal attributions blaming individual failings. The authors further use moderated mediation analysis to demonstrate that two distinct paths explain the effect: causes of need and resulting perceived controllability influence empathy for liberals and outcome efficacy for conservatives. The findings will help charity marketers better understand how donor segments will react to charity appeals.